2019
DOI: 10.1186/s12913-019-4208-9
|View full text |Cite
|
Sign up to set email alerts
|

Rate and predictors for non-attendance of patients undergoing hospital outpatient treatment for chronic diseases: a register-based cohort study

Abstract: Background Failure to keep medical appointments results in inefficiencies and, potentially, in poor outcomes for patients. The aim of this study is to describe non-attendance rate and to investigate predictors of non-attendance among patients receiving hospital outpatient treatment for chronic diseases. Methods We conducted a historic, register-based cohort study using data from a regional hospital and included patients aged 18 years or over who were registered in ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
3
29
0
1
Order By: Relevance
“…This non-signi cant nding is in sharp contrast to other literature [12,39,41,[45][46][47] and may be partly explained by the methodological study design and imbalance between study groups resulting in a high risk of confounding bias. Predictors of non-attendance include gender (male), younger age, unmarried status, low educational level and receipt of long-term welfare payments [48]. While data was collected on a number of these variables, the sample size, particularly in the face-to-face group is insu cient to control for these confounding factors using statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…This non-signi cant nding is in sharp contrast to other literature [12,39,41,[45][46][47] and may be partly explained by the methodological study design and imbalance between study groups resulting in a high risk of confounding bias. Predictors of non-attendance include gender (male), younger age, unmarried status, low educational level and receipt of long-term welfare payments [48]. While data was collected on a number of these variables, the sample size, particularly in the face-to-face group is insu cient to control for these confounding factors using statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐attendance at healthcare appointments is a significant problem across the world. According to NHS England's quarterly review ending in March 2019, the overall non‐attendance rate for general follow‐up hospital outpatient appointments was 8% , with non‐attendance rates appearing similar for people with diabetes compared with other chronic health conditions . Non‐attendance is associated with suboptimal outcomes for the patient, and is a poor use of healthcare resources .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, our study showed lower education level of patients with major limb amputation compared to the general population, which may suggest that barriers such as the ability to understand basic health information, false health beliefs, disease self-management and compliance with treatment, and limited financial recourses may be an issue when dealing with patients with major limb amputation in our region. Furthermore, lower education level has been found to be a predictive factor for higher no-show rates and adherence to treatment [19,20]. Although not the aim of this study, we have also noticed a high no-show rate among amputee patients in our clinic.…”
Section: Education Level N (%)mentioning
confidence: 46%